Melaib Mebase Tegeh: Bentuk Perkawinan Yos Embang - Sumarjayanti, Wayan; Sama, I Nyoman; Darmana, I Ketut (Humanis; Vol 24 No 2 (2020), 2020)
Pedawa village is part of Banjar district, Buleleng regency, which is one of the Bali AgaVillages in the north Bali. Pedawa as the old village has its own uniqueness especially concerning the marriage ceremony in which the local people in that place often called it as Melaib. There are six types of marriages in Desa Pedawa namely melaib ngemaling, melaib ngidih, melaib ngangken, melaib negteg, melaib mebase tegeh, melaib ngerorod (mepekirang).Melaib mebase tegeh is one of the types of marriage for the people of Pedawa Village who shelter Yos Embang which is the procession of the marriage ceremony uses the conditions in the form of banten base tegeh as a symbol for every woman from Yos Embang (local kawitan) who marries out of their clan. The results of this research are expected to provide benefits and development of science in the field of anthropology, especially about marriage. The results of this research showed that melaib mebase tegeh is one of the types of marriage in Pedawa Village, which is implemented by the people in Pedawa vilage that shelter Yos Embang if the women mated out from Yos Embang. Melaib mebase tegeh has the meaning of kinship, religious meaning and cultural. Moreover, if the people who marry girls from Yos Embang do not carry out mebase tegeh ceremony will have an impact on family and community life and have an impact on the belief aspect of the people in Pedawa Village, which shelter Yos Embang.